Effects of sintering temperature on the structure and electrochemical performance of Mg2SiO4 cathode materials - Tamin, S.H.; Adnan, Syed Bahari Ramadzan Syed; Jaafar, Mohd Hilmi; Mohamed, Nor Sabirin (Springer Verlag (Germany), 2018)
The objective of the present study was to investigate the effects of sintering temperature on the structure and electrochemical performance of Mg2SiO4 cathode materials using sol-gel method. X-ray diffraction and Fourier-transform infrared analysis were used to study the structural properties of the materials. The temperatures applied in the sintering process influenced the structure, morphology, as well as particle size distribution of the Mg2SiO4. All samples sintered at temperatures of 900, 1000, and 1100 °C yielded pure Mg2SiO4 compounds consisting of orthorhombic crystalline phase with a space group of Pbnm. Particle size and lattice parameters of Mg2SiO4 samples increased with the increases of sintering temperature due to an increase of the nucleation and crystal growth rates. The cyclic voltammetry analysis showed the presence of redox reaction. This result shows that the Mg2SiO4 material has potential to be used as cathode materials in magnesium rechargeable batteries.